Using an ex-ante entreaty to reduce protest zero bias in stated preference surveys: A health economic case - Ole Bonnichsen; Jacob Ladenburg (Journal of Choice Modelling, 2009)
When prompting respondents to act on the hypothetical markets that are presented to them in stated preference surveys, it is often observed that a proportion of the sample state a zero demand for the good in question even though their genuine demand is positive. Though the literature comes up with some means to calibrate the estimated preferences ex-post, this is far from being unproblematic and uncontroversial. In this paper we test whether a short ex-ante entreaty, presented to respondents in a health economic stated preference survey, can effectively reduce the number of protest zero bids. We first of all find that the protest reduction entreaty significantly reduces the number of protest zero bids in the survey. Furthermore, the results indicate that marginal demand for the individual attributes as well as general preferences do not seem to be influenced by the protest reduction entreaty. Compared to the traditional ex-post calibration of protest zero bids in stated preference surveys, these results suggest that an ex-ante reduction in protest zero bids by using a simple and short entreaty is possible without introducing other types of biases in the survey.
Keywords: 330; choice experiment; health economics; ex-ante protest reduction entreaty; zero bids; bias